Malawi : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents an Update to the Report on the Observance of Standards and Codes on Fiscal Transparency Module for Malawi. The findings reveal that Malawi does not have an elaborate privatization program. The assemblies and municipalities are currently outside of the Integrated Financial Management Information System and, moreover, use a different chart of accounts than the central government. The consolidation of local government budget execution data with those of central government to produce general government reports is crucial for improving the transparency and accountability of government operations.